How employees of Korean franchise restaurants perceive kiosk accessibility for the elderly - Chaeyun Jang (International Telecommunications Society (ITS), 2024)
Digital transformation encompasses fundamental changes in strategy, operations, and culture through the adoption of digital technologies. The franchised restaurant industry in South Korea is undergoing such a transformation, prominently using kiosks for ordering and payment processes. While kiosks enhance convenience and efficiency, they pose challenges for the elderly, who face digital exclusion. South Korea's aging society heightens this issue, as digital exclusion can lead to broader social exclusion. Addressing kiosk accessibility in the private sector, where adoption is rising, necessitates understanding the perceptions of those managing these services. This study adopts Social Representation Theory (SRT) to explore restaurant industry employees' understanding of kiosk accessibility for the elderly. Through semi-structured interviews and core-periphery analysis, the findings reveal both business opportunities and organizational challenges in improving kiosk accessibility for the elderly. This study offers implications for integrating digital inclusion into the digital transformation of private industries.
Keywords: 330; Kiosk; Digital accessibility; Digital inclusion for elderly; Restaurant industry in South Korea; Social representation theory